2017
DOI: 10.1080/01677063.2017.1358270
|View full text |Cite
|
Sign up to set email alerts
|

Role of branchiomotor neurons in controlling food intake of zebrafish larvae

Abstract: The physical act of eating or feeding involves the coordinated action of several organs like eyes and jaws, and associated neural networks. Moreover, the activity of the neural networks controlling jaw movements (branchiomotor circuits) is regulated by the visual, olfactory, gustatory and hypothalamic systems, which are largely well characterized at the physiological level. By contrast, the behavioral output of the branchiomotor circuits, and the functional consequences of disruption of these circuits by abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A reduction in the number or loss of branchiomotor neurons, including FBM neurons, can severely disrupt food intake ( Allen et al, 2017 ; Kassim et al, 2018 ). However, mispositioning of FBM neurons in landlocked mutants did not affect opercular muscle movement ( McArthur and Fetcho, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in the number or loss of branchiomotor neurons, including FBM neurons, can severely disrupt food intake ( Allen et al, 2017 ; Kassim et al, 2018 ). However, mispositioning of FBM neurons in landlocked mutants did not affect opercular muscle movement ( McArthur and Fetcho, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our procedure is extensively described in Allen et al (2017) . Briefly, 10–15 larvae were placed in 5 ml of E3 medium containing 2 mg Larval fish food (Zeigler <100 microns) coated in yellow fluorescent microspheres (Molecular Probes/Thermo Fisher) for 3 h. At the end of the feeding period, larvae were anesthetized with 0.02% tricaine (Western Chemical Inc.), mounted laterally, and scored based on the amount of fluorescent food in the gut.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the olfactory system regulates feeding behaviors in fish (Hamdani, Kasumyan, & Døving, 2001), and dscamb is expressed in both olfactory receptors neurons and the downstream olfactory bulb. Recent studies also demonstrated that molecular or anatomical ablation of branchiomotor neurons in larval zebrafish impairs food capture in a remarkably similar fashion to dscamb loss-of-function (Allen et al, 2017). dscamb is expressed in a subpopulation of larval branchiomotor neurons and their target muscles, but we did not detect obvious defects in the development of NMJs.…”
Section: Discussionmentioning
confidence: 98%
“…Identification of anxiety genes and circuitry in fish is a promising avenue for gaining new insights into human psychiatric disorders. Finally, Allen et al (2017) describe a qualitative but robust feeding assay, and analyze the role of branchiomotor neurons in mediating the intake of food. Ablation of the trigeminal motor neurons or the loss of branchiomotor neurons respectively diminishes or abolishes food intake, indicating that the assay is a sensitive readout of the function of these neurons.…”
Section: Zebrafish: From Genes and Neurons To Circuits Behavior And mentioning
confidence: 99%
“…Historically, behaviors that were amenable to analysis involved simple yet robust reflexes such as startle responses. Although these reflexive behaviors are still important in testing sensory or motor function (Nicolson, 2017;Niklaus & Neuhauss, 2017), other types of behaviors integrating sensory and motor aspects, such as dark avoidance (Wagle, Nguyen, Lee, Zaitlen, & Guo, 2017) and food intake (Allen et al, 2017) are being added to the growing list of quantifiable responses in zebrafish larvae. These developments are facilitating the discovery of novel genes or the generation of new zebrafish models of human neurological diseases.…”
Section: Zebrafish: From Genes and Neurons To Circuits Behavior And mentioning
confidence: 99%